Motivating Students to Learn - Feruza Kurbanova; Sevinch Umid qizi Abdixamitova (Peerian Journals Publishing, 2023)
In this article we aim to have some ideas and suggestions on inspiring and motivating EFL learners. Motivation has been called as the ignored heart of language teaching. It affects effort which affects results and totally students’ abilities. By getting their motivation, you can help students become more proficient in English and increase their ability to learn
Keywords: intimidating; emotional; project-based